Ronald Tannur dan Cerminan Ketimpangan dalam Sistem Peradilan Pidana Indonesia - Dani, Revanis Rahma (Academos, 2025)
Ronald Tannur has emerged as a public figure reflecting the inequality in Indonesia's criminal justice system. This case highlights alleged preferential treatment of perpetrators from elite political backgrounds, potentially violating the principle of equality before the law. This study aims to analyze how the legal process in this case reflects structural, cultural, and institutional inequality in the criminal justice system. The research method used is a sociological juridical approach with a case study approach. The results show strong indications of bias in the legal process, both in terms of treatment by law enforcement officers and media exposure. This study recommends the need for reform of the criminal justice system to ensure independence, transparency, and equality for all citizens.